2021
DOI: 10.1002/app.50623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating PE/PLA interfacial tension using ternary immiscible polymer blends

Abstract: Blending with ethylene-based flexible polymers such as polyethylene (PE) is one of the strategies to toughen poly(lactic acid) (PLA), an inherently brittle biodegradable plastic enjoying growing demands worldwide. Interfacial tension plays a crucial role in blend formulation. Yet several literature reports on the PE/PLA interfacial tension contradict each other, giving~5 mN/m and 11 mN/m. In this work, we demonstrate that the PE/PLA interfacial tension is at least 9 mN/m. We use a cocontinuous PE/polystyrene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In recent years, extensive efforts have been made to the toughening of PLA. For example, petroleum-based derivatives such as polyethylene or chain extenders were compounded with PLA for the purpose of reducing the brittleness. However, the addition of these non-degradable toughing agents inevitably deteriorates the degradability of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive efforts have been made to the toughening of PLA. For example, petroleum-based derivatives such as polyethylene or chain extenders were compounded with PLA for the purpose of reducing the brittleness. However, the addition of these non-degradable toughing agents inevitably deteriorates the degradability of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…In multiphase polymer blends, the morphology of ternary blends can be predicted by understanding the interfacial tension between the blend components. [ 44,45 ] To investigate the interfacial tension of different component in PLA/PBAT/MAM ternary blends, two liquids, water and ethylene glycol, were selected to test the contact angle of neat PLA, PBAT, and MAM at room temperature. The values of interfacial tension for 0.25emγ12, γ23, and γ13 (polymer 1 was PBAT, polymer 2 was PLA, and polymer 3 was MAM) were estimated using the harmonic mean equation [ 46 ] : γ12goodbreak=γ1goodbreak+γ24goodbreak×()γ1d×γ2dγ1d+γ2dgoodbreak+γ1p×γ2pγ1p+γ2p The results are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al demonstrated that experimental value of PLA/PE interfacial tension is at least 9 mN/m at the temperature of 180°C. [ 55 ] In case of PLA/PHB films surface tension was about 3 mN/m indicating higher compatibility of polymers and lower stability of layered structure in such films. However, for these films sufficient fluctuation of surface tension was observed that lead to rather high margin of error in calculation.…”
Section: Resultsmentioning
confidence: 99%